Performance of the Dental Surgeon in the multidisciplinary team in the Intensive Care Unit: Students' perception (Research, Society and Development, 2021)
Objective: To describe the perception of academics, from the tenth period of the Dentistry course of two Higher Education Institutions, about the performance of the dentist (CD) in the Intensive Care Unit (ICU). Methodology: This is a cross-sectional observational study, with the application of a questionnaire for graduates of the Dentistry course, about the performance of the DC in the ICU, the hygiene protocols and the relationship of oral pathogens with systemic diseases. The data were analyzed descriptively and analytically using the chi square test. Results: Of the 71 participants, 87.3% said they knew about the performance of the DC in the ICU. All respondents considered the theme of Hospital Dentistry and the presence of the CD in the multidisciplinary team as important, but 7% considered themselves able to work in this area. Approximately 87% of academics considered requesting complementary exams, prescribing and performing disinfection of the oral cavity as assignments of the DC in a hospital environment. The procedure of drug prescription and requesting complementary exams was most reported by students who had classes on Hospital Dentistry at graduation (p